Plant Species Diversity in Various Agroforestry Patterns in Aik Bual Community Forest, Central Lombok - Fikry, Muhammad Yul; Sarjan, Muhammad; Sjah, Taslim (Protech Biosystems Journal, 2024)
This research discusses the implementation of agroforestry patterns in Aik Bual Community Forest, Central Lombok, which is managed by 260 farmers on 94.45 hectares of land with a 35-year management licence from the Ministry of Environment and Forestry. Agroforestry, which combines agricultural and forestry crops, is focused on maximising productivity and maintaining environmental sustainability. The research was conducted from February to June 2024 with a descriptive method, involving interviews, field observations, documentation and literature studies. Analyses showed that agroforestry patterns increase vegetation diversity and plant structure. Further research is needed to understand the interaction between agroforestry patterns and plant diversity in Aik Bual HKm. The results of this study are expected to support sustainable forest management and provide ecological and economic benefits to the surrounding community.